Lista comentada de plantas vasculares del valle seco del río Patía, suroccidente de Colombia (2015)
Based on herbarium records, data bases and field studies in different localities of the Patia River valley in southwestern Colombia, a total of 297 vascular plants were previously known from this region. In this study the number was increased by 727 to a new total of 1024 species, which is a considerable increase in our knowledge of plant species richness in dry areas of southern Colombia. Those species are distributed among 556 genera in 130 families. Considering the number of species the following families stand out: Fabaceae (45 genera/119 species), Poaceae (52/101), Asteraceae (56/79), Malvaceae (23/44), Cyperaceae (7/41), Euphorbiaceae (10/39), Lamiaceae (13/31) and Solanaceae (9/31). The genera with the largest number of species are: Solanum (19 especies), Cyperus (16), Euphorbia (14), Hyptis (13), Senna (13), Sida (13), Piper (12), Peperomia (11) and Desmodium (10). Herbs are the predominant life-forms (53.77% of total species) followed by shrubs (24.58%). In the valley, pastures and crop fields are predominant; in some sectors, there are bushes and forest fragments in different successional stages; in the southern part, there are thorn bushes, with dominance of succulent plants belonging to the family Cactaceae.